Analisis Penggunaan Model Altman (Z Score) Untuk Memprediksi Kondisi Financial Distress Pada Perusahaan Sektor Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2012-2015 - Lutfiyah, Dewi, Dr. Syamsudin, MM (2016)
This study aims to determine the condition of financial distress property and real estate companies listed on the Stock Exchange (Stock Exchange Indonesia) from 2012 until 2015 using the model of Altman (Z-Score) and to determine the error rate of the financial distress prediction using a model of Altman (Z -Score). Sampling techniques in this study use purposive sampling and non-probability sampling. Data analysis methods use Altman model (Z-Score) and then viewed with an error rate that is owned by the models using the type I and type II errors. The results of the calculation using the model Altman (Z-Score) show the different result prediction at each company and each year, from the 160 companies predicted that 9 companies (5.625%)are predicted financial distress, 25 companies (15.625%)are in the grey area, and 126 companies (78,75%) are predicted non financial distress. Beside it, an error rate prediction Altman model(Z-Score) in 2012 got a type I error of 5% and type II error of 5%. Then in 2013 there were error rate of type I error of 7.5% and type II error of 2.5%. Keywords: Model Altman (Z-Score) and financial distress.